Retrograde Bladder Filling After Outpatient Gynecologic Surgery: A Systematic Review and Meta-Analysis. Issue 2 (February 2022) - Thiel, Peter S.; Mathur, Siddhi; Zakhari, Andrew; Matelski, John; Walsh, Chris; Murji, Ally
Abstract : (Abstracted from Obstet Gynecol 2021;138:647–654) The potential for impaired bladder function after outpatient or inpatient gynecologic surgery has led many centers to require a successful voiding trial before discharge. Partially retrofilling the bladder has been investigated in various gynecologic surgery populations to reduce time spent waiting for passive filling.